DEVELOPMENT OF A MATHEMATICAL MODEL OF THE SYSTEM LIQUID WITH NONLINEAR CHARACTERISTICS - Sergey Aleksandrovich Sidorenko; Roman Valerievich Gerasimov (Вестник Северо-Кавказского федерального университета, 2022)
A mathematical model of the system with nonlinear characteristics for further use in the simulation control system on the basis of artificial neural networks.